(untitled) (Modern education and development, 2024)
Food poisoning is a significant public health concern worldwide, caused by consuming contaminated food or beverages. This article explores effective preventive measures to reduce the risk of foodborne illnesses, emphasizing personal hygiene, proper food handling, and storage practices. By implementing these strategies, individuals can protect themselves and their families from the adverse effects of food poisoning.